The Role of Discipline and Career Development in Improving Employee Work Achievement - Nailin Nikmatul Maulidiyah; Moh. Samsul Arifin; Dian Ary Setyawan (Universitas Negeri Gorontalo, 2021)
This study aims to analyze the effect of discipline and career development on employee work achievement at PT. Bank Syariah Mandiri Jember Brach office. The population in this study is permanent employees at PT. Bank Syariah Mandiri Jember Brach office which numbered 54 employees. The analytical tool used in this study is multiple linear regression analysis to test the effect of the independent variable on the dependent variable. The results showed that the disciplinary significantly influence work achievement at PT. Bank Syariah Mandiri Jember Brach office. Career development significantly influenced work achievement at PT. Bank Syariah Mandiri Jember Branch Office. Simultaneously, discipline and career development significantly influenced work achievement at PT. Bank Syariah Mandiri Jember Branch Office. Keyword: Discipline; Career Development; Work Achievement